A Labeling Strategy for Living Specimens in Long-Term/Super-Resolution Fluorescence Imaging - Han, Yubing; Zhang, Zhimin; Liu, Wenjie; Yao, Yuanfa; Xu, Yingke; Liu, Xu; Kuang, Cuifang; Hao, Xiang (Frontiers in Chemistry, 2021)
Despite the urgent need to image living specimens for cutting-edge biological research, most existing fluorescent labeling methods suffer from either poor optical properties or complicated operations required to realize cell-permeability and specificity. In this study, we introduce a method to overcome these limits—taking advantage of the intrinsic affinity of bright and photostable fluorophores, no matter if they are supposed to be live-cell incompatible or not. Incubated with living cells and tissues in particular conditions (concentration and temperature), some Atto and BODIPY dyes show live-cell labeling capability for specific organelles without physical cell-penetration or chemical modifications. Notably, by using Atto 647N as a live-cell mitochondrial marker, we obtain 2.5-time enhancement of brightness and photostability compared with the most commonly used SiR dye in long-term imaging. Our strategy has expanded the scientist's toolbox for understanding the dynamics and interactions of subcellular structures in living specimens.